Derecho natural y de gentes en Vitoria y Grocio: ¿linajes diferentes? = Natural and International Law in Vitoria and Grotius: Are They of Diverse Pedigree? - Castañeda Salamanca, Felipe (Cauriensia, 2024)
Vitoria and Grotius share neither sceptical nor relativistic positions regarding the existence of natural rights and of peoples that are based on rational human nature or on customs sanctioned by history. However, the differences are considerable if the comparison focuses on the scope of the law of peoples versus the natural law. In this essay it is proposed that, although in Grotius palliatives are formulated against possible norms of the law of peoples that limit, deny or oppose natural law, its margin of application is wide enough to impose utility reasons to arguments of natural justice. Compared to Vitoria, an essential difference would be: although the law of peoples serves to make the natural law applicable, it neither replaces it nor confronts it. If this is so, it could be concluded that Grotius’s approaches to the law of peoples go down a path that for Vitoria would be inconceivable: an eventual predominance of a positivistic law of peoples over a natural law.